GEOLOGICAL AND GEOTECHNICAL RISK MAPPING ASSOCIATED WITH MASS MOVEMENTS IN VIÇOSA (MG) URBAN AREA (Brazilian Geographical Journal, 2014)
Viçosa (MG) presents an undulating terrain with rounding tops hills and steep slopes and thick soils. These characteristics, combined with a process of disordered occupation, resulted in several landslides and erosions processes in recent years. This paper presents the results of a land use and a geological-geotechnical mapping of those urban risk areas, using the methodology proposed by the Brazilian Ministry of Cities. The study area covers all the 51 city urban districts. A total of 101 risk points and 45 risk areas were identified. All risk points and risk areas were ranked throughout the criteria defined on the method. The results proved that the method is a reproducible, reliable, efficient, low cost and easy to apply procedure to determine risk areas. As a result, georrefered information and maps on GIS environment were produced for the entire study area, in a way that can be simply used by municipal authorities.